The Routledge companion to Central and Eastern Europe since 1919 - Webb, Adrian L. (Routledge companions to history, 2008)
The reordering of Europe -- Historical chronology of key events -- Thematic chronologies -- The nation states -- Special topics -- People -- Glossary of specialist terms -- Historiography